Cursed Bunny - Chung, Bora; Hur, Anton Tr. (Gurugram : Hachette, 2017)
"Collection of short stories that blend horror, surrealism, and speculative fiction to take on the patriarchy, capitalism, and reign of big tech"--
Keywords: Korean fiction -- Literature